2017
DOI: 10.1038/s41598-017-03075-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in retinal metabolic profiles associated with form deprivation myopia development in guinea pigs

Abstract: Retinal metabolic changes have been suggested to be associated with myopia development. However, little is known about either their identity or time dependent behavior during this sight compromising process. To address these questions, gas chromatography time-of-flight mass spectrometry (GC-TOF/MS) was applied to compare guinea pig retinal metabolite levels in form deprivation (FD) eyes at 3 days and 2 weeks post FD with normal control (NC) eyes. Orthogonal partial least squares (OPLS) models discriminated bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
12
15
0
Order By: Relevance
“…Baseline refraction and axial component measurements were not different between the right and left eyes of individual animals in each subgroup ( p > 0.05, paired t ‐test). Furthermore, the refraction and axial component values in the left untreated eyes after 2 and 4 weeks were similar to those previously described . These results show that wild‐type guinea pigs undergo emmetropization in an unobstructed vision environment.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Baseline refraction and axial component measurements were not different between the right and left eyes of individual animals in each subgroup ( p > 0.05, paired t ‐test). Furthermore, the refraction and axial component values in the left untreated eyes after 2 and 4 weeks were similar to those previously described . These results show that wild‐type guinea pigs undergo emmetropization in an unobstructed vision environment.…”
Section: Resultssupporting
confidence: 87%
“…We found FD induced a myopic shift in refraction from 2 to 8 weeks of age . Recently, we showed that FD decreased retinal arachidonic acid (ARA) levels in a guinea pig metabolomics study . Such declines are relevant because ARA can be catalysed by cyclooxygenase (COX) to produce prostaglandins including PGF2α .…”
mentioning
confidence: 99%
“…Deprivation in Group II did not interfere with the natural development of the contralateral eye, which is consistent with the findings of other researchers, such as Zhao [35]. Yang et al [36] detected retinal metabolic changes in guinea pigs induced by form deprivation myopia. Although these researchers did not directly measure the SOD and MDA levels, the results they reported represented the retinal metabolite levels.…”
Section: Discussionsupporting
confidence: 88%
“…Defects in mitochondrial complexes I and III as a result of increased superoxide and other reactive oxygen species production (Adam-Vizi 2005) have also been shown to lead to neurodegeneration and subsequent vision loss (Yu et al 2012). Indeed, this finding is consistent with recently published evidence of increased expression of TCA cycle and mitochondrial metabolism genes following negative-lens wear in chick (Riddell et al 2016) and disruptions to TCA cycle metabolite abundance following FDMI in guinea pig (Yang et al 2017) further cementing the importance of the mitochondrial respiratory electron transport chain machinery in myopia development.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 90%